KARTAGENER SYNDROME: A NOT SO RARE PHENOMENON - Abbasi, Munir Ahmad; Suleman, Amir; Ahmed, Naseer; Zaman, Haidar (Journal of Ayub Medical College Abbottabad, 2014)
Background: Kartagener Syndrome is characterized by ciliary dyskinesia and is inherited in autosomal recessive manner. It occurs in 1:20,000-30,000 live births in general population. Its prevalence varies from region to region. Methods: This case series describes four patients of Kartagener Syndrome who were diagnosed in the departments of medicine and pulmonology between year 2009 and 2013. Results: The age of youngest patient was 15 years while the oldest patient was 19 years old. All of them were males. Mean age was 17.5 years. They had presented with history of shortness of breath and productive cough. One of them had presented with rhinorrhea and nasal blockage as the main symptom. Conclusion: Although Kartagener Syndrome is often thought of as a rare disorder, yet it might not be as rare as it is thought of. Considering this and the fact that half of the patients with Kartagener Syndrome do not have situs inversus, large scale studies with family trees are required to trace patients with Kartagener Syndrome. Keywords: Kartagener Syndrome, Autosomal Recessive, Dextrocardia. Bronchiectasis